A model for teaching occupational medicine. (7th September 2015) - Basu, Subhashis; Poole, Jon; Adisesh, Anil
Summary: Background: Despite its relevance to medical practice, occupational medicine has been poorly represented in undergraduate training. This article describes a model for the teaching of occupational medicine to student doctors. Methods: The model comprises two didactic lectures, a student‐selected component (SSC) of five interactive two‐hour sessions and one occupational medicine objective structured clinical examination (OSCE) station in the final MB ChB clinical exam. Interested final‐year students are invited to join the SSC. In session 1, students discuss the scope of occupational medicine practice, which includes a job title–occupational illness quiz, the use of environmental measurements and audiovisual recordings of selected workplaces. Sessions 2–4 involve visits to workplaces such as a laundry, a foundry and a bakery, during which students are asked to record relevant hazards to health, their controls, health effects and how occupational causality might be determined. The final session allows students to present their findings and gain feedback from the occupational physicians and their peers. Occupational medicine has been poorly represented in undergraduate training Results: Twenty‐seven student doctors chose to undertake the SSC in three cycles. Students appreciated the relevance of the specialty and the opportunity to systematically evaluate workplaces. Eighty per cent of all final‐year medical students ( n  = 250) passed the occupational medicine station in the OSCE in 2014. Conclusions: This model for the teaching of occupational medicine links work and medical practice at three stages of undergraduate training and could be adopted by all medical schools. The SSC gave students skills for undertaking illness prevention, workplace evaluation and risk assessment that they had not previously encountered.